(untitled) (The Agriculturists, 2016)
A field experiment was conducted at the Pulse Research Centre of Bangladesh Agricultural Research Institute, Ishurdi, Pabna during Kharif-II season of 2010 to evaluate the efficacy of five herbicides for controlling weeds associated with mungbean (BARI Mung-6). The five herbicides such were: Paraxon (27.6% WV Paraquat dichloride salt), M-clor 5G (Butaclor), Topstar 40 WP (40% Oxadiargyl), Hammer 24 EC (Carfentrazone ethyl), and Panida 33 EC (Pendimethalin) with one control (no herbicide and also no weeding). Weed was collected species wise during weeding at 40 days after sowing from 1 m2 area of each plot and oven dried to estimate weed growth. Among the herbicides, Panida performed the best for reducing the number and dry weight of weeds. The maximum reduction of weed population, the highest weed control efficiency, seed yield (1222 kg ha-1), and maximum economic benefit were also obtained in the treatment receiving Panida 33 EC @ 2 ml L-1. The Agriculturists 2015; 13(1) 127-132